EFFECT OF LOW-DOSE BOTULINUM TOXIN ON HEMIFACIAL SPASM SEVERITY - Wirawan, Clarissa; Siahaan, Yusak Mangara Tua; Suryawijaya, Evlyne Erlyana; Ketaren, Retno Jayantri (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Hemifacial spasm is a condition in which there are unilateral contractions of facial muscles. One of the most effective forms of treatment is botulinum toxin injections. However, this therapy only temporarily relieves symptoms, so repeated injections are necessary. This may place a significant economic strain on patients. Due to this, this study aims to see if low-dose botulinum toxin reduces the severity of hemifacial spasm. Objective: To find out whether there is an effect of low-dose botulinum toxin on the severity of hemifacial spasm. Methods: This study is a paired comparison test with a retrospective cohort design. Primary (HFS Score) and secondary (medical record) data was collected from hemifacial spasm patients at Siloam Hospitals Lippo Village Building B. Results: Data was collected from the 36 patients that fulfilled the inclusion and exclusion criteria. All patients were treated with 10 U or less of botulinum toxin. Results show that for HFS Clinical there was a decrease from a mean of 13,03 ± 2,077 to 6,44 ± 2,311 (p < 0,001), whereas HFS Subjective decreased from a mean of 401,53 ± 229,748 to 95,42 ± 151,607 (p < 0,001). Both components have a p-value < 0,001, making it statistically significant. Conclusion: Low-dose botulinum toxin affects the severity of hemifacial spasm in patients at Siloam Hospitals Lippo Village Building B.